Associations between caregivers’ health behaviours and overweight/obesity among children aged 2–6 years in Beijing, China: a cross-sectional study - Yan Hu; Juan Du; Wenjing Ji; Xueling Li; Aimin Liang; Xiwei Xu (BMJ Open)
Objective To investigate the correlation between caregivers’ health-related behaviours and the prevalence of overweight/obesity among children aged 2–6 years in Beijing city in China.Design Cross-sectional study.Setting Two kindergartens and two community health service centres in Beijing city, China.Participants A total of 1967 children aged 2–6 years were included.Primary and secondary outcome measures Children’s height and weight were measured and body mass index was computed. The caregivers’ exercise health behaviours and dietary health behaviours were assessed using a questionnaire, encompassing the frequency of exercise and the duration of each exercise session, as well as the frequency of consumption of desserts, late-night snacks, and fast food, regular eating habits, and the proportion of meat and vegetables consumed daily. Logistic regression analysis was performed to identify relationships between caregivers’ health-related behaviours and overweight/obesity in children.Results Having caregivers who exercised ≥3 times/week (OR 0.643, 95% CI 0.417 to 0.990) was a protective factor against childhood overweight/obesity compared with having caregivers who exercised <1 time/week; caregivers’ frequent encouragement of children’s participation in physical activity was also a protective factor (OR 0.513, 95% CI 0.352 to 0.749). Additionally, children whose caregivers consumed sweets 2–3 times/week (OR 1.535, 95% CI 1.133 to 2.081) or ≥4 times/week (OR 1.916, 95% CI 1.258 to 2.918), as well as children whose caregivers consumed fast food ≥4 times/week (OR 2.298, 95% CI 1.349 to 3.914), were more likely to be overweight and obesity than children whose caregivers consumed these foods ≤1 time/week. Furthermore, caregivers’ irregular eating habits were positively associated with the occurrence of overweight and obesity in children (OR 1.485, 95% CI 1.056 to 2.089).Conclusion Caregivers’ health-related behaviours were significantly associated with overweight/obesity among children in China. Substantial measures should be implemented to address caregivers’ health-related behaviours to prevent and control childhood overweight/obesity.